2018
DOI: 10.1177/0192513x18793923
|View full text |Cite
|
Sign up to set email alerts
|

“I Walked in on Them”: Young Adults’ Childhood Perceptions of Sex and Nudity in Family and Public Contexts

Abstract: Children’s observation of sex and nudity among parents, peers, or strangers has received limited scholarly attention, mostly because research on sexuality in childhood is difficult or prohibitive to conduct. To address this topic, we conducted a secondary data analysis of 57 human sexuality students’ narratives regarding the emotional and situational contexts of the first sexual image they recalled. We examined those narratives where participants reported that they saw was a “real person” either nude or engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…This confounding of very divergent variables erodes any confidence that nudity itself was the primary driver of the observed effects. More recent relevant research, such as a qualitative study by Allen et al (2018), also follows this trend. Nudity is considered only in the context of sexuality (e.g., walking in on parents having sex), making it difficult to extrapolate the findings to nudity of a non-sexual (or not necessarily sexual) nature, such as would be the case in most naturist environments.…”
Section: Naturism and Childrenmentioning
confidence: 72%
“…This confounding of very divergent variables erodes any confidence that nudity itself was the primary driver of the observed effects. More recent relevant research, such as a qualitative study by Allen et al (2018), also follows this trend. Nudity is considered only in the context of sexuality (e.g., walking in on parents having sex), making it difficult to extrapolate the findings to nudity of a non-sexual (or not necessarily sexual) nature, such as would be the case in most naturist environments.…”
Section: Naturism and Childrenmentioning
confidence: 72%
“…Although many parents acknowledge their responsibility to communicate about sex to their adolescents and diverse groups of adolescents report that they want to hear from their parents (Flores et al, 2015;Frawley & Wilson, 2016;LaSala, 2015), there is substantial evidence that family discourse on sexuality is largely a discourse of silence. Qualitative studies of college students document that their parents are mostly silent about sex, including perceptions of sex and nudity (Allen et al, 2018), masturbation , and menstruation (Allen et al, 2011). These studies found that youth learned more from the media and peers than direct communication from parents (Malacane & Beckmeyer, 2016).…”
Section: Parent-child Sexual Communication: Does Talking Promote or Prevent Sexual Risk-takingmentioning
confidence: 99%
“…The increased ease of access and availability of pornography via computer and mobile devices is not trivial; exposure to sexuality‐related content and pornography via the Internet shapes attitudes about sexual behavior (Wright, 2013; 2018; Wright et al, 2016). Moreover, although many parents recognize that their children might access or be exposed to explicit content via the Internet, they are not always sure how to educate their children about it (Allen et al, 2018; Zurcher, 2017).…”
Section: A Critical View Of Sexuality Education In the United Statesmentioning
confidence: 99%